2013
DOI: 10.1016/j.jnucmat.2013.01.044
|View full text |Cite
|
Sign up to set email alerts
|

ICRF specific plasma wall interactions in JET with the ITER-like wall

Abstract: Abstract.A variety of plasma wall interactions (PWIs) during operation of the so-called A2 ICRF antennas is observed in JET with the ITER-like wall. Amongst effects of the PWIs, the W content increase is the most significant, especially at low plasma densities. No increase of W source from the main divertor and entrance of the outer divertor during ICRF compared to NBI phases was found by means of spectroscopic and W I (400.9 nm) imaging diagnostics. In contrary, the W flux there is higher during NBI. Charge e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(48 citation statements)
references
References 13 publications
3
45
0
Order By: Relevance
“…Experiments were carried out with JET-ILW directly comparing the response of a constant density L-mode plasma to equal amounts of neutral beam (NBI) and ICRH heating, Fig.7. This showed that the power radiated from inside the separatrix (bulk radiation) is much greater with ICRH [32], particularly at low plasma density. Despite this high power loss, it is interesting that the rise in plasma stored energy (not shown) is very similar in the two heating phases.…”
Section: Effect Of Heating Methods On Sourcesmentioning
confidence: 96%
See 1 more Smart Citation
“…Experiments were carried out with JET-ILW directly comparing the response of a constant density L-mode plasma to equal amounts of neutral beam (NBI) and ICRH heating, Fig.7. This showed that the power radiated from inside the separatrix (bulk radiation) is much greater with ICRH [32], particularly at low plasma density. Despite this high power loss, it is interesting that the rise in plasma stored energy (not shown) is very similar in the two heating phases.…”
Section: Effect Of Heating Methods On Sourcesmentioning
confidence: 96%
“…There are tungsten coated tiles in recessed areas of the main chamber of JET-ILW but as yet there is no definite link established to these yet either although a significant W level is still seen in ICRH heated limiter discharges. The cause of the increased radiation during ICRH in JET-ILW remains the subject of ongoing investigation and analysis [32].…”
Section: Effect Of Heating Methods On Sourcesmentioning
confidence: 99%
“…Nevertheless, the strong increase of the W content was unexpected because the antenna limiters are completely made out of Be. Moreover no significant increase of the W source in the divertor, neither at the strike point region nor at the baffle at the divertor entrance was observed, leaving the source yet unidentified [25]. In principle, a change in the (edge) transport could also lead to a higher W concentration, but this seems to be unlikely because copper, which is detected as a trace impurity, does not increase during ICRH.…”
Section: Impurity Sources and Contentmentioning
confidence: 92%
“…However, the strong increase of the W content was unexpected because the antenna limiters in JET are completely made out of Be. Moreover no significant increase of the W source in the divertor, neither at the strike point region nor at the baffle at the divertor entrance was observed, leaving the source yet to be identified [49]. In principle, a change in the (edge) transport could also lead to a higher W concentration, but this seems to be unlikely because copper, which is detected as a trace impurity, does not increase during ICRH.…”
Section: E Icrh Compatibility With W Plasma Facing Componentsmentioning
confidence: 92%
“…A way forward will be the comparison of measured W source profiles with the results of sophisticated RF-codes in order to validate them. An important benchmark will be the reactivation of the JET ITER-like antennas in 2014, which are predicted to cause significantly less impurity influx in JET than the currently existing ones [49]. The H-Mode threshold is consistently reduced by ≈ 30% in AUG and JET.…”
Section: Summary and Conclusion For Itermentioning
confidence: 99%